Wheat Cost-Return Budget in North Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2006)
This publication provides estimated cost and returns for forward farm planning for wheat in north central Kansas.
MF2158_2006_10
Keywords: MF2158; Crops; Economics; MF